2021
DOI: 10.1101/2021.03.25.21254129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-nucleoside reverse transcriptase inhibitor-based combination antiretroviral therapy is associated with lower cell-associated HIV RNA and DNA levels as compared with therapy based on protease inhibitors

Abstract: BACKGROUND: It remains unclear whether combination antiretroviral therapy (ART) regimens differ in their ability to fully suppress HIV replication. Here, we report the results of two cross-sectional studies that compared levels of cell-associated (CA) HIV markers between individuals receiving suppressive ART containing either a non-nucleoside reverse transcriptase inhibitor (NNRTI) or a protease inhibitor (PI). METHODS: CA HIV unspliced RNA and total HIV DNA were quantified in two cohorts (n=100, n=124) of i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
4
1
Order By: Relevance
“…30 Indeed, some studies into reservoir measures like cell-associated HIV RNA and DNA have shown a correlation between these measures and RV, suggesting that RV is at least partially indicative of the reservoir size. 28,31 In contrast to the association between Fiebig stage and RV, no statistically significant impact of Fiebig stage on blips was found in this study, but both blips and ART initiation in the acute phase of infection were relatively rare, precluding a rigorous assessment of their potential relationship.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…30 Indeed, some studies into reservoir measures like cell-associated HIV RNA and DNA have shown a correlation between these measures and RV, suggesting that RV is at least partially indicative of the reservoir size. 28,31 In contrast to the association between Fiebig stage and RV, no statistically significant impact of Fiebig stage on blips was found in this study, but both blips and ART initiation in the acute phase of infection were relatively rare, precluding a rigorous assessment of their potential relationship.…”
Section: Discussioncontrasting
confidence: 92%
“…Moreover, an inverse relationship between CD4 + nadir and HIV‐1 proviral DNA in circulating CD4 + T cells on ART has previously been suggested to either reflect the repopulation of the CD4 + compartment after ART initiation by the relatively highly frequent infected CD4 + T cells harboring HIV‐1 (proviral) DNA (resulting in a larger reservoir) or the incomplete suppression of HIV‐1 replication in PWH with low CD4 + nadirs 30 . Indeed, some studies into reservoir measures like cell‐associated HIV RNA and DNA have shown a correlation between these measures and RV, suggesting that RV is at least partially indicative of the reservoir size 28,31 . In contrast to the association between Fiebig stage and RV, no statistically significant impact of Fiebig stage on blips was found in this study, but both blips and ART initiation in the acute phase of infection were relatively rare, precluding a rigorous assessment of their potential relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al [40] have found significantly lower levels of integrated DNA in resting CD4 + T cells from PWH on protease inhibitor-based regimens compared with NNRTI-based regimens. Moreover, it was recently shown by Pasternak et al [41] that NNRTI-based regimen is associated with lower reservoir size (measured as CA-RNA and CA-DNA) compared with protease inhibitor-based regimens. Additionally, a large study of Darcis et al [42] showed that the probability of having a detectable viral load below 20 copies/ml (target detected) decreases over time and that protease inhibitor-based ART regimens are associated with a significantly higher probability of detectable residual virus compared with NNRTI or INSTI-based ART regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Once integrated, the provirus persists for the lifetime of the cell, and division of an infected cell provides each progeny cell with a copy of the integrated provirus. The reservoir persists primarily through cellular longevity and proliferation [8–12], although replenishment by low-level residual virus replication, for example due to limited penetration of antiretroviral drugs into tissues, has been suggested to contribute as well [13–15].…”
Section: Introductionmentioning
confidence: 99%